The war on drugs: reports from the Irish front - Butler, Shane (Economic & Social Studies, 1997)
The phrase "war on drugs", as a metaphor or shorthand for national and international policies aimed at the prohibition of a range of psychoactive drugs, has been used so widely and for so long that its provenance is no longer entirely clear, but it appears to have had its origins in the United States about 1969, during the first administration of Richard Nixon (Bellis, 1981; Trebach, 1982). This was not, on the face of it, the most auspicious moment for America to commit itself to such a venture, coming, as it did, at the tail-end of the idealistic but unsuccessful "war on poverty" and at the height ofits other unsuccessful, and far more bloody, military engagement in South-East Asia. Bellis provides interesting historical background to this growth in popularity of military rhetoric in the drugs policy field, setting it in the context of the technical achievement represented by the successful landing ofAmerican astronauts on the moon in 1969.
Keywords: Drugs policy; Drug problem; Ireland